Investigation of Drying Curves of Lithium‐Ion Battery Electrodes with a New Gravimetrical Double‐Side Batch Dryer Concept Including Setup Characterization and Model Simulations. Issue 2 (21st December 2020) - Kumberg, Jana; Baunach, Michael; Eser, Jochen C.; Altvater, Andreas; Scharfer, Philip; Schabel, Wilhelm
Abstract : Herein, an experimental setup comprised of a stationary convection dryer (Comb Nozzle Dryer) supplemented by a measurement for gravimetric drying curves is introduced. The drying process of anodes for lithium‐ion batteries is experimentally investigated and compared to modeling results, showing very good agreement for the investigated films. Heat transfer coefficients of the issued impinging nozzles are characterized and measured quantitatively and are used for the drying simulation of the gravimetric drying experiments. In situ temperature changes in the films are measured and presented using an infrared camera setup. Abstract : An experimental setup to measure the drying process of anodes for lithium‐ion batteries in situ is introduced, using a combination of gravimetric and thermal measurements. Experiment is compared to simulation, showing good agreement, enabling the prediction of the drying process of battery electrodes under the knowledge of the drying conditions and the properties of the wet electrode.